Do Focal Seizures Trigger Bilateral Stroke-Like Episodes Which Manifest As Transient Cortical Deafness? - Finsterer, MD, PhD, Josef; Zarrouk-Mahjoub, PhD, Sinda (Journal of Medical Biomedical and Applied Sciences, 2018)
See the PDF